Exosomal miR-16-5p as a target for malignant mesothelioma - Munson, Phillip B. (Sci Rep, 2019)
Malignant mesothelioma (MM) is an asbestos-induced cancer arising on the mesothelial surface of organ cavities. MM is essentially incurable without a means of early diagnosis and no successful standard of care. These facts indicate a deep chasm of knowledge that needs to be filled. Our group recently delved into MM tumor biology from the perspective of exosome-contained microRNAs (miRNAs). We discovered that the most abundant miRNAs in MM cancer exosomes were tumor suppressors, particularly miR-16-5p. This observation lead us to hypothesize that MM cells preferentially secreted tumor-suppressor miRNAs via exosomes. Through separate avenues of potential therapeutic advance, we embarked on an innovative strategy to kill MM tumor cells. We employed small molecule inhibitors to block exosome secretion, thereby reducing miR-16-5p exosome loss and replenishing cellular miR-16-5p leading to reduced tumorigenic capacity and miR-16-5p target oncoproteins CCND1 and BCL2. Additionally, we force-fed MM tumor exosomes back to MM tumor cells, which led to cell death, and a reduction in the same oncoproteins. We recapitulated these results with direct transfection of miR-16-5p, confirmed that this is a cancer-cell specific effect, and elucidated a part of the miR-16-5p mechanism of exosome loading.